Investigation of technological properties of celera root powder obtained by drying with mixed heat supply method - Niemirich, Oleksandra; Ustymenko, Ihor; Mykhailenko, Vladlena; Zuiko (Kulinich), Vira; Sylka, Iryna; Havrysh, Andrey; Skyrda, Olena; Furmanova, Yuliia; Pavliuchenko, Olena; Mamchenko, Liudmyla; Doroshkevych, Ruslan (My University, 2022)
To enrich polyphase-type culinary products, dried food products are used - vegetable and fruit powders. These powders are usually obtained by freeze-drying, convective methods, the method of cold spray drying. To perspective methods of drying include drying with mixed heat supply. At the same time, it is promising to use celery root powder in culinary products. The aim of the work is to study the technological properties of celery root powder obtained by the method of drying with mixed heat supply, to predict its behavior in polyphase food systems. Для збагачення поліфазних кулінарних виробів використовують сушені харчові продукти - овочеві та фруктові порошки. Ці порошки зазвичай отримують сублімаційним, конвективним методами, методом холодної розпилювальної сушки. До перспективних способів сушіння відноситься сушіння зі змішаним теплопостачанням. Водночас перспективним є використання порошку кореня селери в кулінарних виробах. Мета роботи – вивчити технологічні властивості порошку кореня селери, отриманого методом сушіння зі змішаним теплопостачанням, спрогнозувати його поведінку в поліфазних системах харчування.
Keywords: celery root; dispersion; moisture absorption coefficient; microstructure; fat retention capacity; emulsifying ability; корінь селери; дисперсія; коефіцієнт поглинання вологи; мікроструктура; здатність до утримання жиру; емульгуюча здатність; кафедра технології ресторанної і аюрведичної продукції